2014
DOI: 10.1523/jneurosci.2700-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Mediates Neuroprotection against Oxygen-Glucose Deprivation by the Cardiac Glycoside Oleandrin

Abstract: We have previously shown that the botanical drug candidate PBI-05204, a supercritical CO 2 extract of Nerium oleander, provides neuroprotection in both in vitro and in vivo brain slice-based models for focal ischemia (Dunn et al., 2011). Intriguingly, plasma levels of the neurotrophin BDNF were increased in patients treated with PBI-05204 in a phase I clinical trial (Bidyasar et al., 2009). We thus tested the hypothesis that neuroprotection provided by PBI-05204 to rat brain slices damaged by oxygen-glucose de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 42 publications
4
42
0
Order By: Relevance
“…Various neuroprotective agents regulate the synthesis of BDNF. 24,25) Therefore, because EZJ increased BDNF level in the hippocampus, we tested whether transcription and translation are involved in the synaptoprotective effect of EZJ. HFS induced LTP in control slices, but not in Aβ-treated slices (control, 153±3, n=5, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various neuroprotective agents regulate the synthesis of BDNF. 24,25) Therefore, because EZJ increased BDNF level in the hippocampus, we tested whether transcription and translation are involved in the synaptoprotective effect of EZJ. HFS induced LTP in control slices, but not in Aβ-treated slices (control, 153±3, n=5, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that TrkB signaling plays a pivotal role in central nervous system diseases, such as neurodegeneration, psychiatric disorders and ischemia stroke (Castello et al, 2014; Pandya et al, 2014; Van Kanegan et al, 2014). Our previous study suggested that inhibition of protein tyrosine phosphatases could preserve TrkB activation, thus preventing early brain injury after SAH in rat model (Hasegawa et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…TrkB is the primary high affinity receptor for BDNF and BDNF-TrkB axis has been revealed to be neuroprotective involving in various central nervous system disorders, including ischemic injury (Han and Holtzman, 2000; Han et al, 2011; Muller et al, 2008; Van Kanegan et al, 2014), which made BDNF a promising agent for stroke treatment. Therefore, in the current study, we compared the therapeutic effects of HIOC with BDNF after SAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the levels of BDNF in hippocampus are reduced in corticosterone-induced mouse depression model [31]. Increasing data have shown that BDNF has neuroprotective activity [32][33][34]. BDNF is responsible for the structure and function of plasticity in the brain [35], prevents damages to neurons in the brain [36], and plays a key role in neural development and maintenance of the central and peripheral neurons [37].…”
Section: Introductionmentioning
confidence: 99%